2011
DOI: 10.5339/qmj.2011.1.9
|View full text |Cite
|
Sign up to set email alerts
|

Coital Retrograde Menstruation as a Risk Factor for Pelvic Endometriosis

Abstract: To investigate coitus during menstruation as a possible predisposing factor for endometriosis 78 patients were asked about their coital habitus during menstruation and subsequently were examined by ultrasound transabdominally, transvaginally or both, before laparoscopy or surgery. MR! was used in six patients only. There was a statistically significant relationship between endometriosis and coital practice during menstruation. The incidence of endometriosis in patients with history of coitus in menses was 66% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…However, the groups were similar regarding pelvic inflammatory disease. Another study was conducted by Samir et al (18) in Doha, Qatar, to examine sexual activity during menstruation as a predisposing factor for endometriosis. First, participants were asked about sexual activity during menstruation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the groups were similar regarding pelvic inflammatory disease. Another study was conducted by Samir et al (18) in Doha, Qatar, to examine sexual activity during menstruation as a predisposing factor for endometriosis. First, participants were asked about sexual activity during menstruation.…”
Section: Discussionmentioning
confidence: 99%
“…Then, abdominal ultrasound, transvaginal ultrasound, or both were performed before laparoscopy or open surgery. Their results revealed that in the first group: 36 (66%) women tested positive for endometriosis and the second group: 9 (34%) were negative for endometriosis, showing a significant difference between the presence and absence of sexual activity leading to orgasm during menstruation and endometriosis (18). The results of the present study are consistent with the results of Samir’s group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation